GAMBARAN STATUS GIZI ATLET ANGKAT BERAT, ANGKAT BESI DAN BINARAGA KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) PROVINSI RIAU TAHUN 2015 - Jessy Latni G; Yanti Ernalia; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTA great nation can be recognized as a great nation if they haveextraordinary achievement and perfomance on international sport event.Nowadays, there are crisis of sports in Indonesia due to lack of internationalsport achievements and do not show a lot of improvements in national sportdevelopment. Achievement on sports influenced by some factors, one wasbalanced nutrition on athletes. Balanced nutrition on athletes should be givenhuge attention, because giving unbalanced nutrition will cause damage toathletes’ performance, health and sport achievement. The research mainly focusabout nutritional status from heavy lifters, weightlifter and bodybuilder fromIndonesian National Sport Commitee(KONI) Riau province on year 2015. Theresearch design is descriptive cross-sectional. The samples were obtained by totalsampling. The result showed that there were 30 people : 16 heavy lifters, 9weightlifters and 5 bodybuilder; 70% male and 30% female; the average age is atthe end of adolescent age (17-25 yr); Body Mass Index (BMI) mostly overweight(33,3%); the measurement of waist circumference showed that 43,3% has obesity;waist hip ratio showed that 46,6% has obesity, body fat compotition by skinfoldshow abnormality by 63,3% and bioelectrical impedance analysis (BIA) by 90%.The conclusion is athletes’ nutrition status is high normal. Based on the researchKONI suggested to show more attention to athletes’ nutrition.Key words : Heavy lifters, weightlifter, bodybuilder, Indonesian national sportcommitee , nutritional status